2011
DOI: 10.1248/bpb.34.1724
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone Inhibits Interleukin-1.ALPHA. or Tumor Necrosis Factor .ALPHA.-Induced Proinflammatory Cytokine Production via Androgen Receptor-Dependent Inhibition of Nuclear Factor-.KAPPA.B Activation in Rheumatoid Fibroblast-Like Synovial Cell Line

Abstract: Rheumatoid arthritis (RA) is a disease with significant gender differences in its prevalence and clinical features. Interleukin (IL)-1 and tumor necrosis factor (TNF) a a produced by synoviocytes are principle inflammatory and destructive mediators of RA. We found that a potent androgen, 5a a-dihydrotestosterone (DHT) inhibits IL-1a a-induced production and mRNA expression of IL-8, IL-6 and IL-1b b from RA patient-derived fibroblastlike synovial cell line MH7A. Promoter analysis of the IL-8 gene revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
(31 reference statements)
0
13
1
Order By: Relevance
“…We measured TNF-␣ and found that the levels were attenuated in testosterone-treated I/R rats compared with untreated rats with I/R injury. Androgens have been shown previously to be anti-inflammatory (9,19,35). For example, DHT, via the androgen receptor, inhibits IL-1␣ and TNF-␣-induced proinflammatory cytokine production in a rheumatoid cell line (35), and LPS treatment caused increased proinflammatory cytokines in a model of androgen ablation (19).…”
Section: N T-s H a M I N T-i /R -A K I C A S T-i /R -A K I C A S T-mentioning
confidence: 99%
See 1 more Smart Citation
“…We measured TNF-␣ and found that the levels were attenuated in testosterone-treated I/R rats compared with untreated rats with I/R injury. Androgens have been shown previously to be anti-inflammatory (9,19,35). For example, DHT, via the androgen receptor, inhibits IL-1␣ and TNF-␣-induced proinflammatory cytokine production in a rheumatoid cell line (35), and LPS treatment caused increased proinflammatory cytokines in a model of androgen ablation (19).…”
Section: N T-s H a M I N T-i /R -A K I C A S T-i /R -A K I C A S T-mentioning
confidence: 99%
“…Androgens have been shown previously to be anti-inflammatory (9,19,35). For example, DHT, via the androgen receptor, inhibits IL-1␣ and TNF-␣-induced proinflammatory cytokine production in a rheumatoid cell line (35), and LPS treatment caused increased proinflammatory cytokines in a model of androgen ablation (19). Because TNF-␣ is produced by nonimmune cells in the kidney, such as medullary thick ascending limb, the reduction in TNF-␣ may not be contributory to the protection caused by testosterone, but may simply be an indication of less injury to the medulla in the presence of testosterone.…”
Section: N T-s H a M I N T-i /R -A K I C A S T-i /R -A K I C A S T-mentioning
confidence: 99%
“…Aberrant AR activity has been linked with several pathological conditions including male infertility, androgen insensitivity syndrome, spinal and bulbar muscular atrophy, rheumatoid arthritis, hirsutism, baldness, acne, breast and PCa (Gao & Chen 2013, Xu et al 2011). Huggins and Hodges (Huggins & Hodges 1941) first showed the correlation between androgen and prostate tumor growth and based on this pioneer study, ADT became the key treatment method.…”
Section: :12mentioning
confidence: 99%
“…In addition, previous studies have identified the promoter region of MMP1, including the binding site of the transcription factors activator protein-1 (AP-1) and CRE-binding protein (Chambers et al 2013;Reunanen et al 2002). Among them, AP-1 is known to be regulated by TNF-a and IL-1 via nuclear factor-kappa B and Nuclear factor NF-kappa-B inhibitor kinase signalling in several fibroblasts (Cheng et al 2009;Xu et al 2011). Therefore, AP-1 seems to be a candidate transcription factor for the regulation of fibrotic gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was observed using primary HSCs obtained from the liver of two different patients, indicating a generic response between patients. MMP1 gene expression is reported to be induced by TNF-a in many types of fibroblasts (Sasaki et al 2000;Xu et al 2011). However, in our primary HSCs, TNF-a barely induced MMP1 expression.…”
Section: Effect Of Inflammatory Cytokines On Primary Hscsmentioning
confidence: 99%